A pilot study on record reviewing with a priori patient selection. Issue 7 (18th July 2013) - Cihangir, Sezgin; Borghans, Ine; Hekkert, Karin; Muller, Hein; Westert, Gert; Kool, Rudolf B
Abstract : Objectives: To investigate whether a priori selection of patient records using unexpectedly long length of stay (UL-LOS) leads to detection of more records with adverse events (AEs) compared to non-UL-LOS. Design: To investigate the opportunities of the UL-LOS, we looked for AEs in all records of patients with colorectal cancer. Within this group, we compared the number of AEs found in records of patients with a UL-LOS with the number found in records of patients who did not have a UL-LOS. Setting: Our study was done at a general hospital in The Netherlands. The hospital is medium sized with approximately 30 000 admissions on an annual basis. The hospital has two major locations in different cities where both primary and secondary care is provided. Participants: The patient records of 191 patients with colorectal cancer were reviewed. Primary and secondary outcome measures: Number of triggers and adverse events were the primary outcome measures. Results: In the records of patients with colorectal cancer who had a UL-LOS, 51% of the records contained one or more AEs compared with 9% in the reference group of non-UL-LOS patients. By reviewing only the UL-LOS group with at least one trigger, we found in 84% (43 out of 51) of these records at least one adverse event. Conclusions: A priori selection of patient records using the UL-LOS indicator appears to be a powerful selection method which could be an effective way for healthcare professionals to identify opportunities to improve patient safety in their day-to-day work.